Impact of postharvest preservation methods on nutritional value and bioactive properties of mushrooms - Marçal, Sara (2018)
Background: Mushrooms are a good source of protein, dietary fibre, vitamins, minerals and phenolic compounds. However, mushrooms are a very perishable food and the implementation of preservation methods is essential to extend their shelf-life. The preservation methods for mushrooms can be classified into three categories: thermal (drying/freezing), chemical (edible coatings, films and washing solutions) and physical (packing, irradiation, pulsed electric field and ultrasound) processes. These processes can change the nutritional value and bioactive properties of this commodity. Scope and approach: The goal of this review is to critically update and discuss the existing information about the effect of postharvest preservation methods on the nutritional value and bioactive properties of edible mushrooms. Key findings and conclusions: Drying, especially when high temperatures are applied, can cause the degradation of polysaccharides, proteins and flavour compounds. Freezing is one of the best methods to extend mushrooms’ shelf life but cause the loss of vitamins. Edible coatings and films improve the total sugar, ascorbic acid and bioactive compounds preservation during the storage period. Washing solutions decrease amino acids content. Gamma and electron-beam irradiation decrease the unsaturated fatty acid content, whereas UV-B irradiation significantly increases the vitamin D content. However, there is still limited information about the impact of chemical processes, packaging, pulsed electric field and ultrasound on the nutritional composition and bioactive properties of mushrooms, opening research opportunities for future. This review presents technological and economic alternatives that may support the mushroom processing industries to obtain value-added edible mushrooms and related products.